Editorials: Using effective assessment to improve teaching and learning - Mohammed Abujaja, Afishata (2019)
Why is assessment a crucial element in teaching and learning? Why must teachers adopt effective assessment strategies in their practice? Assessment is noted as an important variable in teaching and learning; it is used to understand the extent to which students understand/learn what is taught; teachers also use assessment outcomes to modify their teaching strategies to improve students learning. However, these may prove to be more complex in practice and require some informed strategies to achieve. For example, teachers’ belief systems about assessment is likely to influence how they apply assessment in the classroom which would in turn influence the effect of assessment on students learning. Some assessment beliefs narrowly focus on ‘testing’ and students’ grades/marks which is translated into assessing the extent to which students reproduce what is being taught. Other beliefs view assessment as an integral part of the teaching and learning process in which learning objectives, instructional strategies, student learning styles etc are linked to assessment – assessment focuses on the learner and learning process. Teacher beliefs and practice of assessment invariably influences students’ learning. Hence, depending on how assessment is perceived and applied, it can be a process that can either enhance or impede student learning and achievement. Assessment for learning is one of the most recommended assessment strategies for effective student learning and achievement. In assessment for learning, teaching, learning and assessment are inextricably linked and focuses on the learner and learning. Assessment for learning is based on the assumption that learners use mental models that are complex and constructed from previous experiences to facilitate effective learning, hence assessment should emphasis on learners overall learning experience, use formative assessment and lots of meaningful and timely feedback to students. The opportunities in using assessment for learning includes developing strong and meaningful connection between learning, teaching and assessment; helps learners to focus on the aims of learning rather than the ‘test’ or ‘grade’; provides direction to the teacher in decisions about instructional strategies and materials. Teachers should develop the right belief system and practices of assessment which are consistent with the assessment for learning strategy, they should also continuously examine what they do to ensure that their assessment practices promote effective student learning and achievement. The papers in this issue of the Journal of Researching Education Practice and Theory (JREPT) are case studies from practitioners that examines different forms of student assessments and their impact on students’ learning and achievement.